Analisis Minat Masyarakat Memiliki Asuransi Syariah (Studi Kasus Kabupaten Padang Lawas Kecamatan Aek Nabara) - Marni Siregar; Nurbaiti Nurbaiti; Rahmi Syahriza (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to find out the influence of premiums on public interest in the district. Padang Lawas District. Aek Nabara. To find out the influence of products on public interest in Kab. Padang Lawas District. Aek Nabara. To determine the influence of premiums and products on public interest in the district. Padang Lawas District. Aek Nabara The research used was descriptive qualitative. The research results show that based on the results of the partial test (t test), premiums have a significant effect on public interest in having sharia insurance in Aek Nabara Barumun. Partial test results (t test), Product on public interest in having sharia insurance in Aek Nabara Barumun. Simultaneous test results (F test), premiums and products simultaneously have a significant effect on people's interest in having sharia insurance at Aek Nabara Barumun.